2018
DOI: 10.1115/1.4040165
|View full text |Cite
|
Sign up to set email alerts
|

Does Analogical Distance Affect Performance of Ideation?

Abstract: Identifying relevant stimuli that help generate solutions of desired novelty and quality is challenging in analogical design. To quell this challenge, the multifaceted effects of using stimuli which are located at various analogical distances to the design problem on the novelty and quality of concepts generated using the stimuli are studied in this research. Data from a design project involving 105 student designers, individually generating 226 concepts of spherical rolling robots, are collected. From these d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 26 publications
2
44
1
Order By: Relevance
“…Likewise, by measuring the historical combination frequency (which is opposite to novelty) of the set of prior technologies used in a patented invention, He and Luo (2017) found that the inventions with moderate combination frequency, which Chan et al (2015) termed combination distance , present the highest invention value, measured by the future citations of a patented invention. In addition, Srinivasan et al (2017) allowed designers themselves to search and choose patents from the entire patent database (of Google Patents) for inspiration, and found that designers most frequently obtained inspiration from patents in a medium knowledge distance to the design problem. As such a distance increases, the novelty of generated concepts increases but their quality decreases.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Likewise, by measuring the historical combination frequency (which is opposite to novelty) of the set of prior technologies used in a patented invention, He and Luo (2017) found that the inventions with moderate combination frequency, which Chan et al (2015) termed combination distance , present the highest invention value, measured by the future citations of a patented invention. In addition, Srinivasan et al (2017) allowed designers themselves to search and choose patents from the entire patent database (of Google Patents) for inspiration, and found that designers most frequently obtained inspiration from patents in a medium knowledge distance to the design problem. As such a distance increases, the novelty of generated concepts increases but their quality decreases.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They used a normalized knowledge proximity metric by comparing direct empirical patent citations from one domain to another to the same parameter in randomized patent citation networks. Srinivasan et al [16] used a technology space map to gauge the impact of knowledge distance on design creativity based on a human experiment. They found that engineers are more likely to identify inspirational and useful patents in the domains near their home domains for concept generation, but more novel concepts are inspired by those patents from more distant domains.…”
Section: Patent Technology Network Mapsmentioning
confidence: 99%
“…New technologies are often created via synthesis, analogy or other fashions of creative transformation of existing technologies [24]- [27]. One's ability to discover, learn, adopt and combine existing but previously-unknown technologies to create new ones is conditioned by the knowledge distance between those unknown but existing technologies and the ones that he/she has already mastered [16][28] [29]. One may find it easier and more effective to search and synthesize technologies nearby or within his/her domains of specialization, but more distant domains and technologies may offer more radical innovation opportunities [7]- [9].…”
Section: Innogps: An Application Of the Technology Space Map For Innomentioning
confidence: 99%
“…Patent retrieval has become a necessary and important task in engineering design. Engineers often search for patents related to a design topic (e.g., autonomous vehicle, additive manufacturing) in order to learn the design precedents for inspiration (Fu et al, 2013;Srinivasan et al, 2018). For instance, various methods and tools have been developed to retrieve patents and design information from patent documents to aid in the use of TRIZ (Altshuller and Shapiro, 1956) for innovative problem solving (Cascini and Russo, 2006), design-by-analogy (Fu et al, 2014), function analysis for product platform and product family planning (Song et al, 2018).…”
Section: Introductionmentioning
confidence: 99%